Modern epidemiology and its discontents - Kenneth Rochel de Camargo Jr; Francisco Ortega; Claudia Medina Coeli (Universidade de São Paulo, 2013)
The goal of this article is to present a snapshot of an ongoing debate within epidemiology, pitching opposing sides in the struggle to define the path it should follow in the years to come. The debate among epidemiologists in the mid-90s pitted those who defended the idea that epidemiology should necessarily deal with a wide context against those who believed that science and public health are better served by focusing on the individual level. Ian Hacking's concept of styles of reasoning was used as a theoretical tool. The literature was reviewed using a core set of articles as an entry point, seeking articles that cited them, and then back-tracking the citations of the resulting set in the Scopus database. The main arguments are presented according to levels (ontological, epistemological, axiological and pragmatic), in order to show an even deeper disagreement, in the very conception of science and its relation to social issues and public policy.